Odoo ERP Implementation Point of Sale Module at Mc Cake - Denny Arie Suryo; Syaifudin Abdullah; Teddy Siswanto (Penerbitan Universitas Trisakti, 2021)
Mc Cake is one of the business people in the food industry. Which was founded in Bekasi, West Java. Mc Cake has constraints and problems including the lack of a system that streamlines the time and division of job desk at the company. It also shows that the sales order business process has not been integrated with the sales system at Mc Cake. The process that is currently running from the sale transaction is still done manually. In this problem, the solution considered to be able to handle the problem is by applying the concept of ERP (Enterprise Resource Planning) using the Odoo application with a point of sales module, because the advantages that can be obtained are speed, accuracy, and relatively lower costs compared to other methods. . Odoo is a modular application which means it consists of separate modules but can be integrated with each other. The modules in Odoo include sales, purchase, accounting, point of sale, CRM and marketing. In addition, the business processes carried out on each Odoo module are best practices for the open source class and in general Odoo covers the business processes of MSME trading companies such as Mc Cake.